Improving safety performance in constructions project in Malaysia ( case study : in Kuantan ) - Iradatul Hanis, Abd Hamid (2017)
In both developing countries, the construction industry is considered to be one of the most significant industries in terms of its impact on health and safety of the working population. Construction industry is both economically and socially important. However, the construction industry is also recognized to be the most hazardous. The objectives of this research are to investigate the safety performance in the construction sites. The data were collected from the contractor, consultant and developer by using questionnaire to evaluate the safety performance in construction sites. The questionnaires were distributed to respondents. The result show that there were still a lack of commitment from government, insurance company, the labour ministry, the developers, consultants and also the contractors to improving safety performance on the construction sites. The suggestion is to improve the safety performance on the construction sites. The government should follow up the safety performance by visiting the construction sites. The insurance company should be more active in visiting the construction sites. The developer should be more active toward safety by controlling, visiting the process in construction sites. The contractors have to train the workers and promote the safety culture and follow up the safety performance. The consultant should control all the tools in the construction sites to insure that those tools are safe.